Investigating E-Wallet Adoption Among Gen Z Students: Determinants of Behavioral Intention and Actual Use - Siti Nikhlatus Salma; Ditya Permatasari (Journal of Enterprise and Development (JED), 2025)
Purpose: The primary objective of this study is to examine the determinants influencing individuals’ intentions to adopt digital financial technology, specifically within the context of e-wallet systems.Method: This research employs a quantitative approach, utilizing the Structural Equation Modeling (SEM) framework. A purposive sampling technique was applied to select 216 Generation Z students residing in Malang City as the representative sample.Result: The findings indicate that the behavioral intention to use e-wallets among Generation Z students is significantly shaped by four key factors: perceived usefulness, perceived ease of use, perceived trust, and perceived security. These factors exhibit a synergistic effect in shaping individuals' decisions to adopt e-wallets as digital transaction tools. Furthermore, these factors substantially influence the actual use of e-wallet systems, reflecting the extent to which this technology has been accepted and integrated into the daily lives of Generation Z students.Practical Implications for Economic Growth and Development: This study contributes to economic growth by promoting financial inclusion, enhancing transaction efficiency, and supporting the digitalization of micro, small, and medium-sized enterprises (MSMEs) through the adoption of e-wallets by Generation Z students. Additionally, the increasing utilization of digital payment systems fosters investment opportunities within the fintech sector, thereby encouraging innovation and sustainable economic development.